Perceptions of safety culture vary across the intensive care units of a single institution - Huang, David T; Clermont, Gilles; Sexton, J Bryan; Karlo, Crystal A; Miller, Rachel G; Weissfeld, Lisa A; Rowan, Kathy M; Angus, Derek C (Critical care medicine, 2007)
To determine whether safety culture factors varied across the intensive care units (ICUs) of a single hospital, between nurses and physicians, and to explore ICU nursing directors' perceptions of their personnel's attitudes. Cross-sectional surveys using the Safety Attitudes Questionnaire-ICU version, a validated, aviation industry-based safety culture survey instrument. It assesses culture across six factors: teamwork climate, perceptions of management, safety climate, stress recognition, job satisfaction, and work environment. Four ICUs in one tertiary care hospital. All ICU personnel. We conducted the survey from January 1 to April 1, 2003, and achieved a 70.2% response rate (318 of 453). We calculated safety culture factor mean and percent-positive scores (percentage of respondents with a mean score of > or =75 on a 0-100 scale for which 100 is best) for each ICU. We compared mean ICU scores by ANOVA and percent-positive scores by chi-square. Mean and percent-positive scores by job category were modeled using a generalized estimating equations approach and compared using Wald statistics. We asked ICU nursing directors to estimate their personnel's mean scores and generated ratios of their estimates to the actual scores.Overall, factor scores were low to moderate across all factors (range across ICUs: 43.4-74.9 mean scores, 8.6-69.4 percent positive). Mean and percent-positive scores differed significantly (p < .0083, Bonferroni correction) across ICUs, except for stress recognition, which was uniformly low. Compared with physicians, nurses had significantly lower mean working conditions and perceptions of management scores. ICU nursing directors tended to overestimate their personnel's attitudes. This was greatest for teamwork, for which all director estimates exceeded actual scores, with a mean overestimate of 16%. Significant safety culture variation exists across ICUs of a single hospital. ICU nursing directors tend to overestimate their personnel's attitudes, particularly for teamwork. Culture assessments based on institutional level analysis or director opinion may be flawed.